(untitled) (Anclajes, 2019)
From an interdiscoursive and interdisciplinary perspective, this paper explores different representations with which the Mapuche People of the Gulumapu constructed their processes of cultural and territorial differentiation in tension with the Chilean Nation State. Through heterogeneous discourses -historical, literary, media, testimonial and of political organizations-, a process is expressed that moves from an ancestral unitary vision to strategically assumed modern conceptions, typical of new geopolitical and supranational scenarios, such as those of the State and/or nation. It is concluded that this process mainstream their discourses, which as a whole represent a shared collective imaginary that relates the ancestral notion -Wallmapu- with the modern vision -nation and/or Mapuche State.